6x+6(2x-5)=-10-2x

Simple and best practice solution for 6x+6(2x-5)=-10-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+6(2x-5)=-10-2x equation:


Simplifying
6x + 6(2x + -5) = -10 + -2x

Reorder the terms:
6x + 6(-5 + 2x) = -10 + -2x
6x + (-5 * 6 + 2x * 6) = -10 + -2x
6x + (-30 + 12x) = -10 + -2x

Reorder the terms:
-30 + 6x + 12x = -10 + -2x

Combine like terms: 6x + 12x = 18x
-30 + 18x = -10 + -2x

Solving
-30 + 18x = -10 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-30 + 18x + 2x = -10 + -2x + 2x

Combine like terms: 18x + 2x = 20x
-30 + 20x = -10 + -2x + 2x

Combine like terms: -2x + 2x = 0
-30 + 20x = -10 + 0
-30 + 20x = -10

Add '30' to each side of the equation.
-30 + 30 + 20x = -10 + 30

Combine like terms: -30 + 30 = 0
0 + 20x = -10 + 30
20x = -10 + 30

Combine like terms: -10 + 30 = 20
20x = 20

Divide each side by '20'.
x = 1

Simplifying
x = 1

See similar equations:

| 3x^2-16x+12=0 | | 3y=180 | | (x+40)+(3x-10)=180 | | P+q-p-3q+5= | | 10-7x=106-28x | | 5+7x=11+7x | | 20+5=24 | | 2x-36=100 | | 3(x+3)=(3x+9) | | 30=-11x | | (2x-3)(2x-3)=0 | | 5x-y+150=180 | | -N+(v*b*b)=r | | (x-2)(x+2)=(x-1) | | 2.6z^2-0.9z+2=0 | | m-1=2 | | 5x+12-13= | | 5h-2= | | 141-5x=3x+21 | | -9t-5=-4t+10 | | 6(Z-3)+7Z-3= | | 7x^2-27x-14=0 | | -3X+1=-8X-4 | | -32-4x=8-9x | | a-2=-a-5 | | 139-7x=29x+23 | | .0002x^2-.316x+127.9=7 | | 15y^2+28y+5=0 | | 8+8b=10b | | 13-9x=123-44x | | -16x^2+90x-60=0 | | 12=.50x-8 |

Equations solver categories